FORMULATION AND EFFECTIVENESS OF PLANTAIN PEEL EXTRACT (Musa paradisiaca L) ON MOSQUITO ACTIVITY OF Aedes Sp. - Sri Aprilianti Idris; Angriani Fusvita; Kemal Idris; Eritrianto; Julianti Isma Sari Usman (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health problem transmitted by Aedes sp. mosquitoes. Vector control generally uses synthetic insecticides, but their continued use can lead to resistance and negative impacts on the environment. Plantain peel (Musa paradisiaca L.) is known to contain bioactive compounds such as flavonoids, alkaloids, tannins, and saponins that have the potential as botanical insecticides. This study aims to determine the effectiveness of plantain peel extract (Musa paradisiaca L.) as an insecticide against Aedes sp. mosquitoes through an electric method. This study is an experimental study with a completely randomized design (CRD). Plantain peel extract was tested at four concentrations, namely 0.25%; 0.50%; 0.75%; and 1.00%. Each treatment used 20 Aedes sp. mosquitoes and was repeated three times. The positive control used an electric mat containing 0.01 g/L d-allethrin, while the negative control used distilled water. Observations were made for 24 hours by counting the number of mosquito deaths in each treatment. The results showed that the percentage of Aedes sp. mosquito deaths increased along with increasing extract concentration. A concentration of 0.25% caused 13% mortality, a concentration of 0.50% of 40%, a concentration of 0.75% of 53%, and a concentration of 1.00% of 67%. The positive control showed 100% mortality, while the negative control did not cause mosquito mortality. A concentration of 1.00% provided the highest effectiveness in killing Aedes sp. mosquitoes. Banana peel extract (Musa paradisiaca L.) has insecticidal activity against Aedes sp. mosquitoes through an electric method. Concentrations of 0.75% and 1.00% have met the effective criteria with a mortality rate of more than 50%, so it has the potential to be developed as an alternative environmentally friendly plant-based insecticide.